2007
DOI: 10.1074/jbc.m704878200
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Fibrosis Transmembrane Conductance Regulator Activation Is Reduced in the Small Intestine of Na+/H+ Exchanger 3 Regulatory Factor 1 (NHERF-1)- but Not NHERF-2-deficient Mice

Abstract: Binding of the cystic fibrosis transmembrane conductance regulator (CFTR) chloride channel to the Na؉ /H ؉ exchanger 3 regulatory factor 1 (NHERF-1) and NHERF-2 scaffolding proteins has been shown to affect its localization and activation. We have for the first time studied the physiological role of these proteins in CFTR regulation in native tissue by determining CFTRdependent chloride current in NHERF-1-and NHERF-2-deficient mice. The cAMP-and cGMP-activated chloride current and the basal chloride current in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
61
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(65 citation statements)
references
References 53 publications
3
61
1
Order By: Relevance
“…The mice developed normally, lacked gross phenotypic abnormalities, and exhibited normal mineral-ion homeostasis (Kocher et al, 2003). Like NHERF2-null mice, the absence of NHERF3 was associated with modest reduction of forskolin-induced Na and HCO 3 Ϫ transport (Hillesheim et al, 2007). These results contrast with others showing reduced basal but normal forskolin-induced HCO 3 Ϫ secretion ).…”
Section: /Hcontrasting
confidence: 55%
See 2 more Smart Citations
“…The mice developed normally, lacked gross phenotypic abnormalities, and exhibited normal mineral-ion homeostasis (Kocher et al, 2003). Like NHERF2-null mice, the absence of NHERF3 was associated with modest reduction of forskolin-induced Na and HCO 3 Ϫ transport (Hillesheim et al, 2007). These results contrast with others showing reduced basal but normal forskolin-induced HCO 3 Ϫ secretion ).…”
Section: /Hcontrasting
confidence: 55%
“…No evident morphological, behavioral, mineral-ion, or uric acid wasting phenotype was evident. (Broere et al, 2007;Cunningham et al, 2008). Recent results indicate morphological changes of the intestine of NHERF2-null mice with shorter villi, deeper crypts, and decreased epithelial cell number Murtazina et al, 2011).…”
Section: /Hmentioning
confidence: 99%
See 1 more Smart Citation
“…In additional studies that used NHERF1-and NHERF2-deficient mice, NHERF1 was shown to be critical for apical membrane placement of CFTR in native intestinal epithelium and optimizing cAMP-and cGMP-dependent regulation of CFTR, whereas placing NHERF2 not being of importance for these physiologic roles. 43 NHERF2 confers inhibition of CFTR activity by coupling the lysophosphatidic acid receptor to CFTR on lysophosphatidic acid stimulus. 11,42 Therefore, NHERF proteins follow specific physiologic and pathophysiologic contexts.…”
Section: Discussionmentioning
confidence: 99%
“…The observation that the CHE cells express NHERF-1, but not NHE3, was somewhat unexpected because NHERF-1 was originally thought to be functionally related to NHE3, hence its name. However, NHERF-1 (EBP50) also seems important for the stabilization of apical CFTR (12). NHERF-1 is also expressed in nonepithelial cells like T cells.…”
Section: Disproportionately Robust Secretagogue-induced Membrane Recrmentioning
confidence: 99%